Time series analysis on Indian Mackerel Retail Price in Peninsular Malaysia - Mat Ali, Nur Farhana; Rusiman, Mohd Saifullah; Abdullah, Abdul Wahab (Penerbit UTHM, 2021)
Forecasting fish price has been started for a long time worldwide. The main objective of this study is to predict the monthly retail price of Indian Mackerel in Peninsular Malaysia based on the 9 years data (2007-2015) using two methods which are Box-Jenkins method and Holt’s Linear Trend method. Analyse data showed that the Holt’s linear trend model and autoregressive integrated moving average or ARIMA (0, 1, 1) (0, 0, 0)12 model were proposed. The diagnostic checking for the estimated models confirmed the adequacy of the models. The result of the study showed that the Holt’s linear trend method was become the better model with the lower root mean square error (RMSE) and mean absolute percentage error (MAPE). Later, this method has been used to forecast 3 months upcoming Indian Mackerel price eventhough both models have been proven successful in forecasting the monthly fish prices. In conclusion, the potential result from this study could be used in helping fish farmers in their annual planning of increasing income especially in Peninsular Malaysia.